UPAYA GURU PAI DAN BUDI PEKERTI MENANAMKAN SIKAP TA’ZIM SISWA DI SMP ISLAM TA’ALLUMUL HUDA BUMIAYU - Azam Kelana, Alan; Sholeh, Muhammad (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
In educational institutions, a person who plays an important role in shaping student behavior is an educator, where an educator must teach and provide good moral guidance to students, either in the form of learning materials taught in class or in the form of an approach, and indirectly students will follow the direction taught by their educators, whether in the form of attitudes, materials and morals. One of the good morals that an educator needs to instill in their students is an attitude of ta’zim. The purpose of the researcher in this study is to find out how the efforts of Islamic religious and moral teachers in instilling students' attitudes of respect for teachers. The type of research used in this thesis is field research, namely research activities carried out in the community environment. The data sources used are primary data sources, namely data sources obtained directly from Islamic Religious Education Teachers and students, secondary data sources, namely data sources obtained from books and research related to the problems that the author is studying. The data collection methods used are observation, interview and documentation methods. The data analysis method used is descriptive analysis based on facts. From the results of the research that the researcher studied, it can be concluded that Islamic religious and moral teachers at SMP Islam Ta'allumul Huda Bumiayu in instilling a sense of ta’zim for students use various methods and approaches in the form of a habituation method where the method is that students are accustomed to activities such as greeting and shaking hands with teachers, secondly media and reinforcement through religious activities such as tadarus al-Quran every morning, praying Duha and praying Duhur in congregation and thirdly, namely the integration of ta'zim values in teaching and learning activities such as providing material in the form of polite attitudes in respecting older people